Effects of visual landscape on subjective environmental evaluations in the open spaces of a severe cold city - Chen, Jianru; Jin, Yumeng; Jin, Hong (Frontiers in Psychology, 2022)
The environmental quality and subjective environmental evaluations in urban open spaces are essential. In this study, the effects of building, green, and water landscapes, which are typical visual landscapes, on the subjective environmental evaluations (including thermal sensation and comfort, and overall comfort) in different seasons were analyzed by conducting questionnaire surveys and field measurement in a severe cold city. It was found that the visual landscapes significantly affected subjective environmental evaluations in winter and summer, but there were no effects in the transitional season. In summer, compared with the building and green landscape, the thermal sensation vote in the water landscape was the lowest at 0.4; the differences were 0.3~1.0. However, the thermal comfort vote in the water landscape was 0.6 higher. In winter, the thermal sensation and comfort votes in the water landscape were the lowest, the average evaluation under different UTCI was -2.2, and the results were similar for the overall comfort evaluation. In addition, the subjects believed that green and water landscapes improved thermal comfort and had more significant effects on improving the environmental temperature in the three seasons. Additionally, visual landscape evaluations significantly affect subjective environmental evaluations in summer than in the winter and transitional season; the higher the visual landscape evaluation, the better the thermal and overall comfort.